Object-oriented Information Engineering: Analysis, Design, and Implementation - Montgomery, Stephen (AP Professional, 2012)
Object-Oriented Information Engineering: Analysis, Design, and Implementation discusses design, both its object-oriented and traditional development and analysis, on which the book gives much focus. The book begins with an introduction to information engineering and its phases, object-oriented information engineering, and object orientation. The text then moves on to more specific topics, such as business information requirements; detailed object modeling; business functions and subject areas; and individual object behaviors and object interactions. The book also explains the integration and validation of analysis models; object structure designs; and system designs and its different applications. The text is recommended for undergraduates and practitioners of computer and/or information engineers who want to learn more about object-oriented design, its relation with traditional design, and its analysis. The book is also for those who wish to contribute and conduct further studies in the field of object-oriented design.